Antifungal activity of novel synthetic peptides by accumulation of reactive oxygen species (ROS) and disruption of cell wall against Candida albicans - Maurya, Indresh Kumar; Pathak, Sarika; Sharma, Monika; Sanwal, Hina; Chaudhary, Preeti; Tupe, Santosh; Deshpande, Mukund V.; Chauhan, Virander Singh; Prasad, Rajendra (Peptides, 2011)
In the present work, we investigated the antifungal activity of two de novo designed, antimicrobial peptides VS2 and VS3, incorporating unnatural amino acid alpha,beta-dehydrophenylalanine (Delta Phe). We observed that the low-hemolytic peptides could irreversibly inhibit the growth of various Candida species and multidrug resistance strains at MIC(80) values ranging from 15.62 mu M to 250 mu M. Synergy experiments showed that MIC(80) of the peptides was drastically reduced in combination with an antifungal drug fluconazole. The dye PI uptake assay was used to demonstrate peptide induced cell membrane permeabilization. Intracellular localization of the FITC-labeled peptides in Candida albicans was studied by confocal microscopy and FACS. Killing kinetics, PI uptake assay, and the intracellular presence of FITC-peptides suggested that growth inhibition is not solely a consequence of increased membrane permeabilization. We showed that entry of the peptide in Candida cells resulted in accumulation of reactive oxygen species (ROS) leading to cell necrosis. Morphological alteration in Candida cells caused by the peptides was visualized by electron microscopy. We propose that de novo designed VS2 and VS3 peptides have multiple detrimental effects on target fungi, which ultimately result in cell wall disruption and killing. Therefore, these peptides represent a good template for further design and development as antifungal agents. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Antifungal peptides; Candida albicans; Cell wall; ROS

SWATH-MS reveals that bisphenol A and its analogs regulate pathways leading to disruption in insulin signaling and fatty acid metabolism - Kulsange, Shabda E.; Sharma, Monika; Sonawane, Babasaheb; Jaiswal, Meera R.; Kulkarni, Mahesh J.; Santhakumari, B. (Food and Chemical Toxicology, 2024)
Bisphenol A (BPA) is an endocrine-disrupting chemical (EDC), associated with obesity and insulin resistance. The FDA prohibited the use of BPA-based polycarbonate resins in infant formula packaging; thus, its analogs, viz. Bisphenol S (BPS) and Bisphenol F (BPF) were considered alternatives in epoxy resins, plastics, and food cans. As these analogs might evoke a similar response, we investigated the role of Bisphenols (BPA, BPF, and BPS), on insulin signaling in CHO-HIRc-myc-GLUT4eGFP cells at environmentally relevant concentrations of 2 nM and 200 nM. Insulin signaling demonstrated that Bisphenols reduced phosphorylation of IR and AKT2, GLUT4 translocation, and glucose uptake. This was accompanied by increased oxidative stress. Furthermore, SWATHMS-based proteomics of 3T3-L1 cells demonstrated that Bisphenol-treated cells regulate proteins in insulin resistance, adipogenesis, and fatty acid metabolism pathways differently. All three Bisphenols induced differentially expressed proteins enriched similar pathways, although their abundance differed for each Bisphenol. This might be due to their varying toxicity level, structural differences, and estrogen-mimetic activity. This study has important implications in addressing health concerns related to EDCs. Given that the analogs of BPA are considered alternatives to BPA, the findings of this study suggest they are equally potent in altering fatty acid metabolism and inducing insulin resistance.
Keywords: Bisphenols; Estrogen; Lipid droplet; Mitochondrial beta-oxidation; Oxidative stress; PPAR gamma

Simple freeze-thaw based method for efficient purification of recombinant human proinsulin from inclusion bodies - Rajesh, S.; Jathar, Swaraj; Banarjee, Reema; Sharma, Monika; Palkar, Shivani; Shankar, S. Shiva; Kulkarni, Mahesh J. (Protein Expression and Purification, 2025)
Insulin is a pivotal peptide hormone essential for regulating glucose homeostasis. It has been known for over 100 years, but its production and purification methods are still under improvement. Escherichia coli based bacterial expression system is primarily used for insulin production. The human insulin protein expressed in bacteria usually forms inclusion bodies, complicating the purification process. Traditionally, insulin purification is a timeconsuming process involving urea-based denaturation methods, and various refolding techniques, followed by extensive chromatographic methods. Here, we report an easy and efficient purification of human proinsulin involving freeze-thaw based solubilization method. The extracted proinsulin inclusion bodies are treated with different concentrations of urea, followed by a freeze-thaw based solubilization. The freezing was carried out at various temperatures, mainly -80 degrees C, -20 degrees C, and -196 degrees C to determine the optimum condition for solubilization. Highest solubilization of proinsulin from the inclusion body was achieved with 0.5M urea and -20 degrees C. Further Nickel NTA-based purification was performed, and the purified protein was characterized for disulfide mapping by high-resolution mass spectrometer (HRMS). We also performed glucose uptake assays to validate the functional properties of purified proinsulin. This freeze-thaw based mild solubilization approach is a fast and effective method for getting bioactive proinsulin, which will help further design better purification and processing strategies for insulin production.
Keywords: Diabetes; Disulfide mapping; glucose; insulin; Mass spectrometry

Engineering pichia pastoris as a heterologous platform for non-ribosomal peptide biosynthesis of the β-lactam intermediate δ-(L-α-Aminoadipyl)-L-cysteinyl-D-valine (ACV) - Jogi, Shraddha; Jagtap, Rutuja; Subrahmanyam, Yalamanchili Venkata; Sharma, Monika; Kulkarni, Mahesh; Raghunathan, Anu (ACS Omega, 2026)
The production of nonribosomal peptides (NRPs) in non-native hosts remains challenging due to the size and complexity of the biosynthetic enzymes. Here, we report the first successful reconstruction of the delta-(L-alpha-aminoadipyl)-L-cysteinyl-D-valine (ACV) pathway in Pichia pastoris. By introducing codon-optimized versions of the pcbAB and npgA genes directly into the genome, we were able to rebuild the minimal pathway required for ACV synthesis, which we confirmed using LC-MS/MS. Although the starting strain produced only small amounts of ACV (similar to 5 ng/mL), yields increased 10-fold after adaptive evolution (similar to 50 ng/mL) and further improved with precursor supplementation (similar to 60 ng/mL). Transcriptomic analysis showed that the engineered strain reorganized its metabolism to meet the energy and precursor demands of NRPS activity. Overall, this study suggests that P. pastoris can serve as a practical, proof-of-concept host for complex NRP biosynthesis and lays the groundwork for future engineering of beta-lactam pathways.